2004
DOI: 10.1088/0031-9155/49/6/003
|View full text |Cite
|
Sign up to set email alerts
|

Sonoelastographic imaging of interference patterns for estimation of the shear velocity of homogeneous biomaterials

Abstract: The shear wave velocity is one of a few important parameters that characterize the mechanical properties of bio-materials. In this paper, two noninvasive methods are proposed to measure the shear velocity by inspecting the shear wave interference patterns. In one method, two shear wave sources are placed on the opposite two sides of a sample, driven by the identical sinusoidal signals. The shear waves from the two sources interact to create interference patterns, which are visualized by the vibration sonoelast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 19 publications
0
90
0
1
Order By: Relevance
“…It has been shown that shear wave interference patterns can be produced using two opposing mechanical sources and, subsequently, visualized in real-time using sonoelastographic imaging techniques [31]. More importantly, when sources are excited at slightly offset frequencies, interference patterns slowly propagate through tissue at an apparent velocity proportional to the frequency difference.…”
Section: Principles Of Crawling Wave Sonoelastographymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that shear wave interference patterns can be produced using two opposing mechanical sources and, subsequently, visualized in real-time using sonoelastographic imaging techniques [31]. More importantly, when sources are excited at slightly offset frequencies, interference patterns slowly propagate through tissue at an apparent velocity proportional to the frequency difference.…”
Section: Principles Of Crawling Wave Sonoelastographymentioning
confidence: 99%
“…Due to a relationship between particle vibrational response and received Doppler spectral variance [29], the amplitude of low frequency shear waves propagating in tissue can be visualized in real-time using sonoelastography to detect regions of abnormal stiffness [30]. In a more recent sonoelastographic development, it was shown that interfering shear waves could produce slowly propagating interference patterns with an apparent velocity much less than (but proportional to) the underlying true shear velocity [31]. Termed crawling waves, they are generated using a pair of mechanical sources vibrating at slightly offset frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Regions where the vibration amplitude is low are shown as dark green, while regions with high vibration are shown as bright green. Wu et al (2004) applied sonoelastography to measure shear wave velocity of interference patterns. Following the experimental setup illustrated in Figure 1, two vibration sources of identical frequencies and amplitudes were applied to the testing sample.…”
Section: Theory Shear Wave Interference Patternsmentioning
confidence: 99%
“…The crawling waves generated by a pair of external shear wave sources (Piezo Systems, Cambridge, MA, USA) interfere with each other, appearing as moving parallel stripes in sonoelastography images. An earlier paper (Wu et al 2004) proved that the spacing between the parallel strips is half of the shear wave wavelength. With the measured shear wave wavelength and the known driving signal frequency, we are able to calculate the shear wave velocity, and thus the Young's modulus of the material.…”
Section: Introductionmentioning
confidence: 99%
“…∇) ⃗ ( 53 ) Considerando a direção z para o campo aplicado ( ⃗ = (0,0, )) e o momento magnético (mz) das nanopartículas paramagnéticas, a força magneto motriz atuando na direção z será: = ( . ∇) ( 54 ) Quando uma nanopartícula está localizada em um meio diamagnético tal como tecidos ou mimetizadores de tecidos, o momento magnético é reescrito de acordo com a equação 45.…”
Section: -33unclassified